Organic-modified ZnS nanoparticles as a high-performance lubricant additive. Issue 10 (1st March 2023) - Kumara, Chanaka; Armstrong, Beth; Lyo, Inwoong; Lee, Hong Wook; Qu, Jun
Abstract : Oil-miscible and oil-transparent organic modified ZnS nanoparticles were developed as an antiwear additive to improve lubricant performance. Abstract : Lubricants are essential in transportation vehicles and industrial machinery to improve the lifetime of moving components. Antiwear additives in lubricants significantly minimize wear and material removal due to friction. While a wide range of modified and unmodified nanoparticles (NPs) have been extensively studied as lubricant additives, fully oil-miscible and oil-transparent NPs are essential to improve performance and oil visibility. Here, we report dodecanethiol-modified oil-suspendable and optical-transparent ZnS nanoparticles (NPs) with a nominal diameter of 4 nm as antiwear additives to a non-polar base oil. The ZnS NPs formed a transparent and long-term stable suspension in a synthetic polyalphaolefin (PAO) lubricating oil. The ZnS NPs in PAO oil at 0.5 or 1.0 wt% concentration demonstrated excellent friction and wear protection. The synthesized ZnS NPs showed 98% wear reduction compared to the neat PAO4 base oil. For the first time, this report showed the outstanding tribological performance of the ZnS NPs benchmarked to the commercial antiwear additive zinc dialkyldithiophosphate (ZDDP) with an additional 40–70% wear reduction. Surface characterization revealed a ZnS-derived self-healing polycrystalline tribofilm (<250 nm), which is key to superior lubricating performance. Our results indicate the potential of ZnS NPs as a high-performance and competitive antiwear additive to ZDDP, which has broad transportation and industrial applications.